Replacement of glass-former B2O3 by GeO2 in amorphous host evidenced by optical methods - Pisarska, Joanna; Pisarski, Wojciech (Photonics Letters of Poland, 2017)
Two completely different glass-host matrices containing lead, i.e. borate and germanate glasses doped with erbium were studied. Replacement of glass-former B2O3 by GeO2 in amorphous host was evidenced by optical methods. The luminescence decay from the 4I13/2 upper laser state of Er3+ ions is relatively short, whereas up-converted emission signal is reduced definitely in borate glass containing lead due to its high B-O stretching vibrations. The results indicate that germanate glasses containing lead are promising for near-infrared luminescence and up-conversion applications. Full Text: PDF References R. Balda, A. Oleaga, J. Fernandez, J.M. Fdez-Navarro, "Spectroscopy and frequency upconversion of Er3+ ions in lead niobium germanate glasses", Opt. Mater. 24, 83 (2003). CrossRef H. Yamauchi, Y. Ohishi, "Spectroscopic properties of Er3+-doped PbO?Ga2O3?GeO2 glass for optical amplifiers", Opt. Mater. 27, 679 (2005). CrossRef W.A. Pisarski, Ł. Grobelny, J. Pisarska, R. Lisiecki, W. Ryba-Romanowski, "Spectroscopic properties of Yb3+ and Er3+ ions in heavy metal glasses", J. Alloys Compd. 509, 8088 (2011). CrossRef M.B. Saisudha, J. Ramakrishna, "Effect of host glass on the optical absorption properties of Nd3+, Sm3+, and Dy3+ in lead borate glasses", Phys. Rev. B 53, 6186 (1996). CrossRef C.K. Jayasankar, V. Venkatramu, S. Surendra Babu, P. Babu, "Luminescence properties of Dy3+ ions in a variety of borate and fluoroborate glasses containing lithium, zinc, and lead", J. Alloys Compd. 374, 22 (2004). CrossRef W.A. Pisarski et al. "Luminescence spectroscopy of rare earth-doped oxychloride lead borate glasses", J. Lumin. 131, 649 (2011). CrossRef M. Kochanowicz, W. Mazerski, J. Żmojda, K. Czajkowski, D. Dorosz, "Green upconversion emission in tellurite optical fibre codoped with Yb3+/Er3+", Phot. Lett. Poland 5, 35 (2013). CrossRef J. Dorosz, "Novel constructions of optical fibers doped with rare ? earth ions", Ceramics 86 (2005). CrossRef J. Żmojda, D. Dorosz, M. Kochanowicz, J. Dorosz, "Spectroscopic properties of Yb3+/Er3+ - doped antimony-phosphate glasses for fiber amplifiers", Phot. Lett. Poland 2, 76 (2010). CrossRef J. Dorosz, R. S. Romaniuk, "Development of Optical Fiber Technology in Poland", INTL J. Electron. Telecom. 57, 191 (2011). CrossRef Q.Y. Zhang et al. "Effects of PbF2 doping on structure and spectroscopic properties of Ga2O3?GeO2?Bi2O3?PbO glasses doped with rare earths", J. Appl. Phys. 99, 033510 (2006) CrossRef W.A. Pisarski, G. Dominiak-Dzik, W. Ryba-Romanowski, J. Pisarska, "Role of PbO substitution by PbF2 on structural behavior and luminescence of rare earth-doped lead borate glass", J. Alloys Compd. 451, 220 (2008). CrossRef M. Sołtys, J. Pisarska, L. Żur, T. Goryczka, W.A. Pisarski, "Influence of M2O3 (M = Al, Ga) glass modifiers on structure, thermal and spectroscopic properties of rare earth ions in lead phosphate based systems", Proc. SPIE 9228, 92280A (2014). CrossRef J. Janek, J. Pisarska, W.A. Pisarski, "Rare earth doped lead-free germanate glasses for modern photonics", Phot. Lett. Poland 6, 71 (2014). CrossRef W.A. Pisarski et al. "Infrared-to-visible conversion luminescence of Er3+ ions in lead borate transparent glass-ceramics", Opt. Mater. 31, 1781 (2009). CrossRef J. Pisarska, L. Żur, W.A. Pisarski, "Optical spectroscopy of Dy3+ ions in heavy metal lead-based glasses and glass?ceramics", J. Mol. Struct. 993, 160 (2011). CrossRef L. Żur, M. Sołtys, J. Pisarska, W.A. Pisarski, "Absorption and luminescence properties of terbium ions in heavy metal glasses", J. Alloys Compd. 578, 512 (2013). CrossRef W.A. Pisarski, L. Żur, M. Kowal, J. Pisarska, "Enhancement and quenching photoluminescence effects for rare earth ? Doped lead bismuth gallate glasses", J. Alloys Compd. 651, 565 (2015). CrossRef M. Shojiya, Y. Kawamoto, K. Kadono, "Judd?Ofelt parameters and multiphonon relaxation of Ho3+ ions in ZnCl2-based glass", J. Appl. Phys. 89, 4944 (2001). CrossRef